Henry Wai-Chung Yeung: Interconnected Worlds. Global electronics and production networks in East Asia. Stanford University Press, Innovation and Technology in the World Economy Series, Stanford, 2022. - Benedek, József (Észak-magyarországi Stratégiai Füzetek, 2023)
-